Formation of Religious Character through the Boarding School Program among Students at MAN 1 Jepara - Nur Cholid; Laqoniyatu Hilma (At Turots: Jurnal Pendidikan Islam, 2025)
The character crisis among today’s young generation, particularly teenagers pursuing education in schools or madrasas, is evident through numerous cases such as bullying, brawls, social issues and orther incidents. This affects students’ character values, necessitating character. This research aims to analyze religious character building through the boarding school program for students at MAN 1 Jepara. The research focuses on 1) How religious character is built through the boarding school program for students at MAN 1 Jepara; 2) What are the supporting and inhibiting factors in religious character building through the boarding school program for students at MAN 1 Jepara. This study employs a descriptive qualitative approach. Data collection methods include observation, interviews, and documentation. The research findings show that religious character building is implemented through three main methods: 1) Habituation, which includes five-time congregational prayers, Quran recitation, tahsin, ziyadah and diniyah studies; and 3) Disciplinary measures or punishment for rule visiolations. Supporting factors in building religious character through the boarding school program include caregiver/murobbi role modelling, boarding school environment and infrastructure facilities. Meanwhile, inhibiting factors in religious character building through the boarding school program include differences in student backgrounds, communication with parents, student mindsets and bullying in boarding schools.